Chiral, pH-sensitive polyacrylamide hydrogels: Preparation and enantio-differentiating release ability. (26th June 2015) - Cheng, Ru; Liu, Jie; Xie, Peng; Wu, Youping; Deng, Jianping
Abstract: Both pH-sensitive hydrogels and chiral hydrogels have evoked large interest in recent years. In the study, we designed and prepared a novel type of hydrogels simultaneously showing pH-sensitivity and chirality. Such hydrogels were prepared by free radical co-polymerization using N -acryloyl-l -alanine as chiral hydrophilic monomer and octadecyl acrylate as hydrophobic monomer, with K2 S2 O8 as initiator and N, N ′-methylenebisacrylamide as chemical cross-linking agent. The obtained hydrogels exhibited remarkable pH-sensitive swelling ability in water. The optical activity of the hydrogels was characterized using circular dichroism spectroscopy. More interestingly, the hydrogels showed enantio-differentiating release ability towards proline enantiomers, in which d -proline was preferentially released. The hydrogels also demonstrated remarkable enantio-differentiating release ability toward chiral drug ibuprofen. Graphical abstract: Highlights: Chiral, pH-sensitive hydrogels contained both chemical and physical cross-linking. The hydrogels showed enantio-differentiating release performance toward prolines. The hydrogels showed enantioselective release toward racemic ibuprofen drug.